Optimalisasi Pembelajaran Deep Learning pada Implementasi Kurikulum Merdeka di Sekolah Dasar: Analisis Literatur - Yulius Efendi; Riska Meisyi Putri; Aprizon Dika Putra; Anggia Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the Independent Curriculum requires learning that develops students' critical, creative, and reflective thinking skills, one of which is through a deep learning approach. This study aims to systematically analyze the application of deep learning in the implementation of the Independent Curriculum in elementary schools through a literature review. The study employed a qualitative approach with a literature review design of relevant and reputable journal articles, proceedings, and scientific publications. Data were collected through documentation studies and analyzed using content analysis and thematic analysis techniques. The results indicate that deep learning can increase student active engagement, critical thinking skills, and the quality of meaningful and contextual learning through the application of project-based strategies, problem-solving, and reflection. Successful implementation is influenced by teachers' pedagogical competence, school environmental support, and the availability of learning resources. While the main obstacles include limited teacher understanding and disparities in facilities. This study concludes that optimizing deep learning requires strengthening teacher capacity and ongoing support from the education system for effective implementation of the Independent Curriculum in elementary schools.